Income Tax for Microenterprises in the COVID-19 Pandemic: A Case Study on Ecuador - Paredes-Torres, Maribel (2022)
In this work, we analyze the income tax in Ecuador in 2020, which was affected simultane-ously by two factors: the economic crisis caused by COVID-19 and the implementation of a new tax system. The objective is to evaluate the effects of these factors on the economic status of a group of taxpayers and the difference in tax payments compared with previous periods. A quantitative study was carried out, collecting financial data from 30 microenterprises for three fiscal periods. We also analyze the relationship between sales and the taxes paid in the same year, as well as the difference between the previous regime and the system applied in the first year of the pandemic to determine income tax. The results indicate an increase in the tax paid despite a noticeable decrease in sales due to confinement and other sanitary measures. In addition, we verified a significant difference between the two analyzed regimes, mainly because the pandemic regime calculates the tax based solely on income and does not consider expenses. We conclude that 43.33% of the microentrepreneurs we analyzed concluded the fiscal year with an accounting loss. This implies a debt for the following period and the risk of bankruptcy in the future.